2013
DOI: 10.3329/cmoshmcj.v12i3.16713
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Descriptive Study of Etiology and Clinical Pattern of Liver Abscess : 50 Cases

Abstract: Background: The liver is the organ most subjected to the development of abscesses and made up 48 % of all visceral abscesses' and 7% of all intra abdominal abscesses. Liver abscess should be suspected when there is a combination of fever, leucocytosis, constitutional symptoms, and pain in the right upper quadrant, and tenderness over the liver or right lower rib cage. The liver is affected by a number of local and disseminated infections; their frequency and types vary considerably around the world. Parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Pus culture was negative in all their cases, thus supporting our findings. 7 The second most common benign liver lesion on FNA and Cellblock in the present study was a pyogenic abscess. Similar studies conducted by Lodhi et al and Abbasi et al showed 18% and 24.8% cases of pyogenic abscess respectively.…”
Section: Discussionmentioning
confidence: 50%
“…Pus culture was negative in all their cases, thus supporting our findings. 7 The second most common benign liver lesion on FNA and Cellblock in the present study was a pyogenic abscess. Similar studies conducted by Lodhi et al and Abbasi et al showed 18% and 24.8% cases of pyogenic abscess respectively.…”
Section: Discussionmentioning
confidence: 50%